Pemanfaatan E-Book sebagai Sumber Informasi Digital di UPT Perpustakaan UIN Alauddin Makassar - Nasrullah, Nasrullah; Tawakkal, Tawakkal; Basri, Muhammad Nur Ikhsan; Hidayatullah, Fauzan; Majidah, Majidah (Universitas Sebelas Maret Library, 2023)
This study aims to investigate the utilization of digital collections (e-books) as a source of information at the Library UPT of Alauddin State Islamic University Makassar and the challenges faced in their utilization. The study adopts a descriptive approach with a qualitative method. Primary data was collected through observation, interviews, and documentation from 2 librarians and 10 library users. Data processing and analysis techniques involved data reduction, data presentation, and drawing conclusions. The results of the study indicate that the utilization of digital collections (e-books) at the Library UPT of Alauddin State Islamic University Makassar has been implemented. There are 435 active members and a total of 7,800 readers utilizing the library's digital collection (e-books). Factors influencing the utilization of digital collections (e-books) include user needs, user interest, and the completeness of the collection. The digital collection (e-books) have significantly contributed to supporting academic tasks and thesis writing, providing easy access without restrictions of time and space. With a collection of 1,764 digital titles, the information needs of users are well fulfilled through the provided digital collection (e-books). More library users utilize digital collections (e-books) compared to printed books. However, challenges faced by users in the utilization of digital collections (e-books) include a lack of promotion by the library to users, inadequate network infrastructure, and a time-consuming registration process. To enhance the utilization of digital collections (e-books), the library needs to improve effective promotion to users, address network issues, and expedite and simplify the registration process. By taking these steps, it is expected that users will find it easier and more convenient to utilize the digital collection (e-books) as a source of information at the Library UPT of Alauddin State Islamic University Makassar.